"It Will Do More than Just Annoy the Protestants": The 19991 Northern Ireland Census and the Irish Language. Issue 3 (3rd July 2022) - Cooley, Laurence
Abstract: Making use of archival sources, this article reconstructs the decision-making process behind the addition of an Irish language question to the 1991 Northern Ireland census. It highlights a distinctive feature of the case: whereas such decisions usually result from state-society interactions, the question was rather suggested by the Irish government, using the role granted to it by the 1985 Anglo-Irish Agreement to act as a kin state to promote the cultural interests of nationalists in Northern Ireland. Officials in Belfast were initially reluctant to accede to this request, though feared refusal might result in a repeat of nationalist boycotts of previous censuses. Ultimately, the precedent set by language questions employed in Wales and Scotland made exclusion hard to justify and officials reluctantly agreed to the question, coming to see the precedent as a useful argument with which to fend off potential unionist opposition, which they feared might have resulted in a rival boycott. The inclusion of the question has subsequently had significant consequences for political claims-making about the status of the Irish language in Northern Ireland.